Recontextualizing Article 97 of the Indonesian Compilation of Islamic Law: A Maqasid-Based Analysis of Judicial Practices in Joint Property Disputes - Supian Daelani; Wasman Wasman; Sugianto Sugianto; Samsudin Samsudin; Randy Vallentino Neonbeni (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
Article 97 of the Compilation of Islamic Law (KHI) stipulates that if a marriage ends due to divorce, each surviving widow or widower is entitled to half (50%) of the joint property, unless otherwise stipulated in the marriage agreement. This study aims to review (recontextualize) the application of Article 97 of the KHI from a justice perspective, particularly in cases where the husband and wife's contributions to the acquisition of property are unequal, or where one party (particularly the wife) bears a double burden. The research method used is normative legal research with a conceptual approach and a case-based approach (judgment decisions). The results indicate that the rigid application of Article 97 of the KHI (equal division) often results in substantive injustice, particularly when the wife acts as the primary breadwinner or a housewife who works hard beyond basic obligations while the husband is negligent.  Recontextualization of this article is necessary by shifting the paradigm from "equal distribution" (equality of portion) to "division based on real contribution" (proportional justice) and the principle of Maqasid Sharia (benefit). Supreme Court Judge Decision No. 266 K/AG/2010 provides the basis for the division of joint assets not necessarily being 50:50, but rather taking into account the extent of each party's contribution to the acquisition of the joint assets.